2017
DOI: 10.3233/ch-160207
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin improves microcirculation in experimental sepsis

Abstract: This study demonstrates that BH4 improves capillary density and inflammation in two separate models of sepsis. BH4 may represent a novel adjunct in the treatment of sepsis and septic shock in clinical practice. Further dose-finding studies and clinical trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Considering the deleterious effects of overproduction of endogenous NO in sepsis, several NOS inhibitors, including selective and nonselective, have been developed, and the therapeutic efficacy and safety of these compounds have been widely investigated. Unfortunately, these studies have produced mixed results; thus, whether to treat sepsis by NOS inhibitors is still a matter of debate [ 111 , 163 ]. While a phase II trial showed that L-NMMA, a nonselective NOS inhibitor, improved systemic vascular response in patients with septic shock, a phase III trial conducted subsequently was terminated.…”
Section: Gaseous-mediator-based Therapeutic Strategy For Sepsis/septi...mentioning
confidence: 99%
“…Considering the deleterious effects of overproduction of endogenous NO in sepsis, several NOS inhibitors, including selective and nonselective, have been developed, and the therapeutic efficacy and safety of these compounds have been widely investigated. Unfortunately, these studies have produced mixed results; thus, whether to treat sepsis by NOS inhibitors is still a matter of debate [ 111 , 163 ]. While a phase II trial showed that L-NMMA, a nonselective NOS inhibitor, improved systemic vascular response in patients with septic shock, a phase III trial conducted subsequently was terminated.…”
Section: Gaseous-mediator-based Therapeutic Strategy For Sepsis/septi...mentioning
confidence: 99%
“…Until now, there has been no reliable and practical intervention that can improve or prevent microcirculatory dysfunction. Most previous studies on interventions to improve microcirculation were small, single-center studies showing inconsistent results [99][100][101][102][103][104][105]. Traditional hemodynamic interventions to improve macrocirculation may not improve and may even impair microcirculation.…”
Section: The Present and Future Of Microcirculationmentioning
confidence: 99%
“…[21] Intestinal microcirculation disorders can be reversed by Tolllike receptor 4 (TLR4) antagonists. [22]…”
Section: Other Pathogenesesmentioning
confidence: 99%
“…[41] Selective inhibition of adenosine triphosphate (ATP)-sensitive potassium (K ATP ) channels in vasodilatory shock by continuous infusion of glipizide could partially restore vasomotor tone in endotoxemic rats and improve systemic hemodynamics in septic rats. [42] Tetrahydrobiopterinl, [22] toll-like receptor World J Emerg Med, Vol 13, No 3, 2022 4 (TLR4) antagonist, [43] and desmopressin [44] have an effect on improving the intestinal microcirculation. There are individual reports of vasopressin V1A receptors, [45,46] physostigmine, [47] and dehydroepiandrosterone combined with orthovanadate, [48] showing that they could improve microcirculation.…”
Section: Other Treatmentsmentioning
confidence: 99%